Transformation of Islamic Education: Empirical Study on Traditional, Modern, and Globalized Societies - Aisy, Salwa Rihadatul; Supriadi, Udin; Budiyanti, Nurti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2024)
This study examined significant changes in Islamic education within traditional, modern, and globalization-era societies. The study aimed to identify and analyze the shifts in Islamic education across these social contexts, including the emerging challenges and opportunities. Employing a qualitative descriptive method, this research gathered relevant data through literature review and empirical analysis. Findings indicate that traditional communities tend to prioritize the informal transmission of religious values, contrasting with modern society's approach, which has adopted technology and implemented more systematic educational strategies. Meanwhile, in the globalization era, despite efforts toward more inclusive and adaptive Islamic education, gaps in access and quality remain. This research concluded that the challenges in Islamic education have become increasingly complex over time, necessitating appropriate adaptations within each social context. The main contribution of this study lies in providing in-depth insights into the relevance of Islamic education across diverse contexts and recommendations to improve its access and quality in alignment with global demands.